Electrochemotherapy in the treatment of melanoma - Wichtowski, Mateusz; Murawa, Dawid (Contemporary Oncology/Współczesna Onkologia, 2018)
Electrochemotherapy is a new therapeutic option for patients with locally spread melanoma. It is based on the phenomenon of reversible electroporation, i.e. a transient increase in permeability of cell membranes under the influence of an appropriately modulated electric field. This allows multiplication of toxicity of a cytostatic agent entering the tumour cell. It is highly effective, especially in the palliative treatment of cancers located in the integument of the human body (skin and subcutaneous tissue). Available literature provides a mandate both for the application of this method in the aforementioned cases as well as for further work on its development. This paper focuses on reviewing the literature concerning the use of electrochemotherapy in the treatment of melanoma.